The Effect of Earnings Opacity and Tax Avoidance on Companies Value - Sinekti, Adesia Gifara; Satyawan, Made Dudy (AKRUAL: Jurnal Akuntansi, 2021)
Companies in Indonesia have carried out many earnings modification practices where earnings modification is the attitude of management to choose accounting policy with various purposes or motives, namely opportunistic motives and efficiency motives. Opportunistic motive if the modification aims to provide welfare for management, while the efficient motive is if it aims to increase the market value of the company. This study functions to analyze the effect of earnings opacity , tax avoidance , price earnings ratio, return on assets, and leverage on the value of food and beverage companies listed on theIDX in 2018-2020, with a sample of 15 companies based on the purposive sampling method. The research method used is a quantitative method. Analysis of the information used in this study is multiple regression analysis. The results prove that earnings opacity and tax avoidance have a negative effect on companies value